The dangerous book for boys - Iggulden, Conn (Collins, 2007)
A collection of entertainments geared toward boys, containing accounts of famous battles, William Shakespeare quotations, games, and instructions for activities such as building a go-cart, cutting flint heads, making an electromagnet, and folding the "greatest paper airplane in the world.".